TUJUAN ALLAH MENCIPTAKAN LEBAH DAN MANFAAT MADU PADA KESEHATAN MANUSIA - Naufal Maulana; Marwin Marwin; Ali Akbar (PT. Saha Kreasi Indonesia, 2025)
This article discusses the purpose of Allah's creation of bees and the health benefits of honey, based on the Qur'anic verses in Surah An-Nahl (16:68–69). The study uses a qualitative library research method, analyzing Qur'anic texts, Hadith, and scientific literature. The findings show that bees were created as a sign of Allah's greatness and to provide great benefits to humans—through honey as syifā'un lin-nās (a healing for mankind) and through their role in maintaining ecological balance. Scientifically, honey contains active compounds that act as antibacterial, antioxidant, and natural healing agents. In conclusion, the creation of bees reflects spiritual, ecological, and health wisdom, demonstrating the perfection of Allah's creation.